2021
DOI: 10.3390/biomedicines9111686
|View full text |Cite
|
Sign up to set email alerts
|

B Lymphocyte-Deficiency in Mice Causes Vascular Dysfunction by Inducing Neutrophilia

Abstract: B lymphocytes have been implicated in the development of insulin resistance, atherosclerosis and certain types of hypertension. In contrast to these studies, which were performed under pathological conditions, the present study provides evidence for the protective effect of B lymphocytes in maintaining vascular homeostasis under physiological conditions. In young mice not exposed to any known risk factors, the lack of B cells led to massive endothelial dysfunction. The vascular dysfunction in B cell-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In a study conducted on mice with a B cell deficiency, it was reported that there was an increase in the number of neutrophils in the circulating blood. 22 Patients with snAIH exhibited higher neutrophil counts than patients with spAIH. This finding supports the suggested involvement of B cell deficiency in the pathogenic mechanism of snAIH.…”
Section: Discussionmentioning
confidence: 92%
“…In a study conducted on mice with a B cell deficiency, it was reported that there was an increase in the number of neutrophils in the circulating blood. 22 Patients with snAIH exhibited higher neutrophil counts than patients with spAIH. This finding supports the suggested involvement of B cell deficiency in the pathogenic mechanism of snAIH.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies have shown that B cell production is significantly reduced in the bone marrow of aged mice and humans [ 48 ], Frasca et al found that aging downregulates B cell type switching in humans and mice [ 49 ]; in addition, hypercholesterolemia Apoe-/- mice and low-density lipoprotein-deficient mice have also shown that protective immunity of B cells can delay the progression of atherosclerosis, while the lack of B cells increases the occurrence of atherosclerosis [ 50 , 51 ]. Further studies have found that the lack of B cell in mice can lead to vascular endothelium dysfunction by inducing the increase of neutrophils, thereby leading to vascular diseases [ 52 ]. These studies demonstrate the importance of B cells in the development of atherosclerosis and may have a more significant impact on large vessel atherosclerosis than in carotid atherosclerosis, but more work is needed to confirm this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of humoral immunity in AS development is little known to us since B cells are occasionally detected in atherosclerotic plaques. Studies on B-cell dynamics in atherosclerotic mice have yielded contradictory results: one indicates B cells mitigate AS, while another suggests B cells exacerbate it following B cell depletion ( 35 38 ). This discrepancy underscores the need for a comprehensive examination of B cell populations and their specific functions.…”
Section: Immuno-interaction Along With the Processes In Asmentioning
confidence: 99%